Alterations of agency in hypnosis: A new predictive coding model - Martin, Jean-Rémy; Pacherie, Elisabeth (Psychological review, 2019)
Hypnotic suggestions can lead to altered experiences of agency, reality, and memory. The present work is primarily concerned with alterations of the sense of agency (SoA) following motor suggestions. When people respond to the suggestion that their arm is rising up all by itself, they usually have a feeling of passivity for their action. The mechanisms leading to such alterations of the SoA are still controversial. We propose a theoretical model based on the framework of predictive coding: The view that the brain constantly generates hypotheses that predict sensory input at varying levels of abstraction and minimizes prediction errors either by updating its prior hypotheses-perceptual inference-or by modifying sensory input through action-active inference. We argue that suggested motor behavior and the experience of passivity accompanying it can be accounted for in terms of active inference. We propose that motor suggestions optimize both proprioceptive predictions and actual proprioceptive evidence through attentional modulation. The comparison between predicted and actual sensory evidence leads to highly precise prediction errors that call for an explanation. The motor suggestion readily supplies such an explanation by providing a prior of nonagency to the subject. We present this model in detail and discuss how it relates to, and differs from, other recent models of hypnosis. We compare its predictions with the predictions derivable from these other models. We also discuss the potential application of our predictive account to reality and memory alterations in hypnosis and offer an explanation of interindividual differences in hypnotic suggestibility. (PsycINFO Database Record (c) 2019 APA, all rights reserved).